Aggregate Signs in The Linguistic Landscape of Pandawa Beach: A Semiotic Pespective - Nurul Khasanah; Rizal d Syifa (Pusat Kegiatan Belajar Masyarakat (PKBM) Sambi Poleng, 2023)
This research examines aggregate signs in the public space of Pandawa Beach from a semiotic perspective. Pandawa Beach is a tourist attraction in Bali with buildings and outdoor signs built around high cliffs and aggregate elements. The use of aggregate signs on Pandawa Beach has particular meanings related to infrastructure, regulation, commercial, and transgressive. This research was conducted on November 17, 2022, and December 12, 2022, in Kutuh village, South Kuta, precisely on Pandawa beach. There were 37 aggregate signs from three buildings on Pandawa Beach: the entrance gate, lighthouse, and Segara inner temple. The findings show that the aggregate signs are used on notice boards, building legal signs, notice signs, icons, indexes, commercial signs, and transgressive signs. The languages ​​used in aggregate signs are Indonesian, English, Mandarin, and Balinese script. Apart from that, two aggregate signs were found that had undergone changes in line with Bali Regional Regulation No.1 2018 concerning the use of Balinese script: the lighthouse building and Pura Dalem Segara. In addition, aggregate signs show the characteristics of a place, as shown by the icon of the Pandawa knight statue on Pandawa Beach, Bali.